2016
DOI: 10.5301/ejo.5000763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ex-PRESS Mini Glaucoma Shunt Implantation with Preoperative Intracameral Bevacizumab Injection in Refractory Neovascular Glaucoma

Abstract: Ex-PRESS mini glaucoma shunt implantation with preoperative bevacizumab injection may be an effective alternative procedure for refractory neovascular glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 6 10 One study showed that EX-PRESS implantation combined with preoperative bevacizumab injection might be effective in patients with NVG; however, that study suffered from the limitations of a small sample size and lack of a control group. 11 The EX-PRESS glaucoma filtration device versus trabeculectomy (XVT) study, 8 which excluded patients with NVG, compared clinical outcomes of EX-PRESS implantation and trabeculectomy alone and found similar mean IOP, number of medications, and surgical success rates between the two groups. Moreover, the overall surgical complication rate was lower in the EX group than in the Trab group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 10 One study showed that EX-PRESS implantation combined with preoperative bevacizumab injection might be effective in patients with NVG; however, that study suffered from the limitations of a small sample size and lack of a control group. 11 The EX-PRESS glaucoma filtration device versus trabeculectomy (XVT) study, 8 which excluded patients with NVG, compared clinical outcomes of EX-PRESS implantation and trabeculectomy alone and found similar mean IOP, number of medications, and surgical success rates between the two groups. Moreover, the overall surgical complication rate was lower in the EX group than in the Trab group.…”
Section: Discussionmentioning
confidence: 99%
“… 6 10 However, subjects in most of the previous studies did not have NVG. Although a few reports showed that EX-PRESS implantation reduced IOP postoperatively in eyes with NVG, 11 , 12 its therapeutic effect in patients with NVG is not fully understood. To the best of our knowledge, there have been no reports comparing the effects of EX-PRESS implantation with those of trabeculectomy alone in patients with NVG.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the 1 year surgical results of Ex-PRESS® mini shunt surgery with trabeculectomy for NVG patients. Since, past studies about the results of Ex-PRESS® mini shunt surgery for NVG included less than 10 patients [15, 16], or non-comparative one [17], this is the first report of such a comparison for NVG, and therefore should have important relevance to current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…All the studies in this meta-analysis used intravitreal injections, but other approaches such as subconjunctival and anterior chamber injections are also used clinically. Guven Yilmaz et al 42 reported that drainage valve implantation with preoperative anti-VEGF anterior chamber injection may be an effective alternative for refractory NVG. Bhagat et al 43 found that intracameral injection was the most effective for IOP control.…”
Section: Discussionmentioning
confidence: 99%